Pengaruh self-efficacy dan self-regulated learning terhadap nilai IPK mahasiswa pendidikan matematika - Juandi, Dadang; Sariningsih, Ratna; Susilowaty, Nora; Arifin, Zaenal (IKIP Siliwangi, 2025)
Students in mathematics education programs often face challenges that require strong self-belief and the ability to manage their own learning in order to achieve optimal academic performance. This study investigates the influence of self-efficacy and self-regulated learning on students’ Grade Point Average (IPK), focusing on three objectives: (1) the direct effect of self-efficacy on IPK, (2) the direct effect of self-regulated learning on IPK, and (3) the indirect effect of self-efficacy on IPK mediated by self-regulated learning. A quantitative approach with path analysis was employed, involving 40 Mathematics Education students selected through simple random sampling. Data were collected via validated and reliable questionnaires, and analyzed using SPSS and SMART-PLS v.4. The results indicate that the direct influence of self-efficacy on IPK is weak and statistically insignificant. In contrast, self-regulated learning shows a significant and meaningful direct effect on IPK. Furthermore, self-efficacy strongly influences self-regulated learning, which in turn positively affects IPK, confirming an indirect relationship. It is concluded that fostering both self-belief and regulatory learning strategies is essential to improving academic outcomes in higher education.